ANALISIS PENERAPAN METODE SHARED READING DALAM MENINGKATKAN LITERASI MEMBACA SISWA KELAS II DI SD NEGERI 5 KARANGREJO GROBOGAN TAHUN PELAJARAN 2025/2026 - Nadya Rahma Windarini; Heru Sri Suryanti, Hera; Restuningsih, Ani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Analysis of the Application of the Shared Reading Method to Improve Reading Literacy of Second-Grade Students at SD Negeri 5 Karangrejo in the 2025/2026 Academic Year. Thesis. Surakarta: Faculty of Teacher Training and Education, Slamet Riyadi University, Surakarta, 2026. This research was motivated by the low reading literacy skills of second-grade students, such as reading difficulties, low comprehension of reading content, and a lack of interest in reading. This study aims to determine the application of the shared reading method in improving reading literacy in second-grade students at SD Negeri 5 Karangrejo and to determine students' responses to the method. This study used a descriptive qualitative approach. The research subjects consisted of the principal, second-grade teachers, and second-grade students at SD Negeri 5 Karangrejo. Data collection techniques were conducted through observation, interviews, and documentation. Data validity was ensured using source triangulation and technical triangulation, while data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the application of the shared reading method is carried out through pre-reading, during reading, and post-reading activities. This method has a positive impact on improving students' reading literacy, indicated by increased reading fluency, comprehension of reading content, reading interest, and students' confidence when reading in front of the class. Despite obstacles such as differences in students' reading abilities and limited reading materials, the shared reading method is considered effective in helping improve the reading literacy of second-grade students at SD Negeri 5 Karangrejo.